(untitled) - Quinn, Thomas (New York, 2004)
Few parties have undergone such comprehensive organizational change as the Labour Party since 1983. Labour's organization once institutionalized the political exchange between office-seeking politicians and the party's policy-seeking trade union paymasters. Using accessible rational choice models, Thomas Quinn explores how consecutive election defeats prompted party leaders to modernize this structure to regain voters' trust, reducing union influence in policymaking, parliamentary candidate selection and leadership contests. The price may be a centralized party vulnerable to membership exit and union funding cuts.
Keywords: Labour party (Great Britain),Labour party (Great Britain)-; History,Reorganization